2013
DOI: 10.4081/pr.2013.e5
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Congenital Anomalies in Newborn: A Hospital-Based Study

Abstract: Birth defects, encountered frequently by pediatricians, are important causes of childhood morbidity and mortality. Birth defects can be classified according to their severity, pathogenic mechanism, or whether they are involving a single system or multiple systems. This hospital-based prospective descriptive study highlights the prevalence of Congenital Anomalies (CAs) in one year among live born neonates delivered in Zagazig University Hospital (Egypt). All women giving birth to viable babies were included. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
67
6
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 8 publications
(9 reference statements)
16
67
6
3
Order By: Relevance
“…These findings were similar to the results in other studies (14,15,17) . This was followed by central nervous system anomalies.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were similar to the results in other studies (14,15,17) . This was followed by central nervous system anomalies.…”
Section: Discussionsupporting
confidence: 93%
“…[10][11][12] However, there are variations between different studies which could be explained by the effect of different racial, ethnic and social factors in various parts of the world; or different geographical factors prevailing in our region. In our study, malformations were more common in twins than in singletons (2.84% versus 1.85%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported that the rate of kinship relationships among the parents of CA-afflicted infants was 58.5% in Birjand (28) and 40% in Saudi Arabia (28). Studies in the Middle East and North Africa also confirmed the greater risk of CAs among parents with consanguineous marriage (6,(35)(36)(37)(38). Moreover, a study in Ardebil reported a significant correlation between parental kinship relationship and CA affliction among infants (10).…”
Section: Discussionmentioning
confidence: 85%